2013
DOI: 10.1589/jpts.25.1497
|View full text |Cite
|
Sign up to set email alerts
|

On the Functional Capacity and Quality of Life of Patients with Acromegaly: Are They Candidates for Rehabilitation Programs?

Abstract: [Purpose] This study compared patients having active acromegaly with those having controlled acromegaly in terms of peripheral muscle strength, body composition, and functional capacity. We also examined the associations between these measures. [Methods] A total of 14 patients with active acromegaly, 12 patients with controlled acromegaly, and 12 healthy controls were subjected to isometric dynamometry, surface electromyography, electrical bioimpedance, and a six-minute walk test. [Results] The active acromega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Acromegaly is a chronic disorder which, in addition to metabolic and cardiovascular impairment, is well known for its detrimental effects on functional capacity, sense of well‐being and fatigue . Previously, we showed that exercise may lessen the negative self‐image people with acromegaly .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Acromegaly is a chronic disorder which, in addition to metabolic and cardiovascular impairment, is well known for its detrimental effects on functional capacity, sense of well‐being and fatigue . Previously, we showed that exercise may lessen the negative self‐image people with acromegaly .…”
Section: Discussionmentioning
confidence: 96%
“…It has a wide range of systemic involvement, varying from soft tissue and skin to cardiovascular changes . Consequently, it has detrimental effects on both the functional performance and psychosocial status of the cases involved . Although acromegaly is amenable to treatment, not all complications are reversible and even after remission, quality of life may not be restored …”
Section: Introductionmentioning
confidence: 99%
“…In this study, exercise capacity was examined using the 6MWD and was lower than the predicted values. Several factors may be involved in the reduced exercise performance in patients with acromegaly, including cardiopulmonary dysfunction, musculoarticular involvement, and metabolic changes 6 , 8 ) . In addition, the systemic impairments caused by acromegaly can result in a more sedentary lifestyle, thereby resulting in an overall loss of muscle strength and a consequent reduction in functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the six-minute walk test (6MWT) has been promoted as a method to analyze various multisystemic diseases, and because it is a submaximal test, it can assess the functional capacity of an individual when performing their normal daily living activities 7 ) . Nevertheless, there are still few studies that have used the 6MWT on acromegalic patients 8 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation